2004
DOI: 10.1016/j.jacc.2003.08.064
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nonselective non-aspirin non-steroidal anti-inflammatory medications on the risk of nonfatal myocardial infarction and their interaction with aspirin

Abstract: In the absence of aspirin use, NANSAIDs are associated with reduced odds of MI. In those using aspirin, NANSAIDs do not provide additional protection. Additional study is needed to determine the clinical impact of using NANSAIDs along with aspirin for cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 24 publications
2
98
0
Order By: Relevance
“…Of them, two articles based on the General Practice Research Database (GPRD) (García Rodríguez et al 2000;Watson et al 2002) and another one based on a case-control study in Philadelphia (Kimmel et al 2004) were excluded because their study population overlapped with that of more recent versions. However, we did consider additional sub-analyses if they were provided only in the earliest versions (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of them, two articles based on the General Practice Research Database (GPRD) (García Rodríguez et al 2000;Watson et al 2002) and another one based on a case-control study in Philadelphia (Kimmel et al 2004) were excluded because their study population overlapped with that of more recent versions. However, we did consider additional sub-analyses if they were provided only in the earliest versions (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…However, we did consider additional sub-analyses if they were provided only in the earliest versions (e.g. RR estimates for individual tNSAID) (Kimmel et al 2004). In addition, one study originally excluded for not presenting results with non-users as a reference was used in a comparison of Naproxen users with users of other tNSAIDs (Rahme et al 2002).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspirin given 2 hours before a daily dose of ibuprofen successfully inhibits platelet aggregation 1 ; however, ibuprofen administered 3 times per day competitively prevents aspirin from accessing its target serine and inhibiting platelet aggregation ( Figure 1C). Some post hoc analyses [5][6][7] suggested that patients taking both aspirin and ibuprofen had more cardiovascular events than patients taking either drug alone, although others found no clinical risk. 8,9 J.D.…”
Section: The Aspirin-ibuprofen Drug-drug Interactionmentioning
confidence: 99%